Operational developments during the establishment of Secunda Collieries - C. J. Cloete; J. T. Collins (The Southern African Institute of Mining and Metallurgy, 1986)
Secunda Collieries forms part of Sasol Coal, the coal division of the Sasol Group of companies, and already produces 29 Mt of coal per annum from its four collieries: Twistdraai, Brandspruit, Bosjesspruit, and Middelbult. The successful establishment of this mining complex was achieved only through a unique team spirit in which the central services and the decentralized teams under the leadership of the mine management of each of the four mines played an important role. The Secunda mining complex has now reached the optimization phase, during which the mining cost, productivity, safety, and quality of work become as important as production. The setting of priorities and problem solving over the long, medium, and short term are essential for improving the performance of the four collieries. Management had to adapt to the fast-changing environment during the enormously fast build-up of production. The major challenges in the environment were posed by the frequent dolerite intrusions, the extremely hard cutting conditions caused by carbonated nodules and thin sandstone intrusions in the coal seam, and excessive roof and face pressure in some areas due to semi-massive sandstone formations in the rock strata.